Asuhan Keperawatan Pada Pasien Hipertensi Dengan Intervensi Terapi Senam Hipertensi Terhadap Penurunan Tekanan Darah - Yeni Gumiati; Meynur Rohmah; Dwi Wahyuni (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: Aging Is The Main Cause Of Hypertension, Which Is Caused By Physiological Changes That Weaken The Heart's Pumping Power And Make The Large Arteries Stiff And Unable To Expand As The Heart Pumps Blood Through Them. Exercise Has The Effect Of Lowering Blood Pressure In People With Hypertension Due To Movement (Yesi Arisandi And Mardiah, 2022). Hypertension Exercise Is One Way Of Maintaining Physical Fitness Or Physical Exercise That Can Be Done To Reduce Body Weight And Manage Stress So That It Can Increase The Body's Metabolic Activity And Can Stimulate Heart Activity And Can Strengthen The Heart Muscles. (Siti Santy Sianipar And Desi Kumala Farianing Putri, 2018). Method: The Method For Writing This Final Scientific Work Is In The Form Of A Literature Review By Examining Journals That Discuss The Effect Of Hypertension Exercise On Reducing Blood Pressure In People With Hypertension. Results: Based On The Table Above, The Author Recommends That Patients Carry Out Hypertension Exercises Regularly For Three Consecutive Days From January 9 To January 11 2024. There Are Differences Between Conditions Before And After Implementation. The Patient Data Before Implementation Was That The Patient Said Both Legs Were Swollen, While The Patient Data After Implementation Was That The Patient Said Complaints Of Swelling In The Legs Were Reduced And Blood Pressure Began To Fall, Namely 140/90 Mmhg, So It Can Be Concluded That There Is An Effect Of Hypertension Exercise Therapy On Reducing Blood Pressure. Blood In Hypertensive Sufferers. This Is In Accordance With The Journal That The Author Studied, Namely According To Rima Berliana Purbaningrum (2020).